1989
DOI: 10.1002/neu.480200303
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Golgi apparatus in sorting of materials to opposite ends of frog rod retinal photoreceptors

Abstract: We have studied the rod cells of retinas of Rana pipiens by phosphatase cytochemistry and immunocytochemistry. We find that the Golgi apparatus of these cells, although different in its intracellular distribution from that of other neurons, has a cis-trans organization like that of other neurons as regards morphological features and the distribution of phosphatase activities. Antibodies against opsin bind to several sacs of the rod Golgi apparatus, especially those at the trans side of the Golgi stack. This su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Studies on the developmental expression of synaptophysin and synaptoporin in the central nervous system revealed that these proteins are present not only in mature terminals but also in outgrowing axons (Bergmann et al, 1991Scarfone et al, 1991;Ovtscharoff et al, 1993; this study) and, unexpectedly, in the cytoplasmic bridge connecting retinal photoreceptor cell bodies with the rod component (Schmied and Holtzman, 1989), in dendrites of the continuously regenerating olfactory receptor neurons and, transiently, in dendrites of developing hippocampal pyramidal neurons (this study). While synaptic vesicles in outgrowing axons could serve as a reservoir for subsequent synaptogenesis, synaptic vesicle membrane antigens in developing dendrites are unlikely to contribute to synaptic organelles.…”
Section: Discussionmentioning
confidence: 58%
“…Studies on the developmental expression of synaptophysin and synaptoporin in the central nervous system revealed that these proteins are present not only in mature terminals but also in outgrowing axons (Bergmann et al, 1991Scarfone et al, 1991;Ovtscharoff et al, 1993; this study) and, unexpectedly, in the cytoplasmic bridge connecting retinal photoreceptor cell bodies with the rod component (Schmied and Holtzman, 1989), in dendrites of the continuously regenerating olfactory receptor neurons and, transiently, in dendrites of developing hippocampal pyramidal neurons (this study). While synaptic vesicles in outgrowing axons could serve as a reservoir for subsequent synaptogenesis, synaptic vesicle membrane antigens in developing dendrites are unlikely to contribute to synaptic organelles.…”
Section: Discussionmentioning
confidence: 58%
“…3F,G) microscopy. This region probably corresponds to the location of the Golgi apparatus, where synaptic vesicle membrane biogenesis, and thus accumulatipn of SVPs, may occur (Tixier-Vidal et al, 1988;Janetzko et al, 1989;Schmied and Holtzman, 1989). This was supported by double-labeling experiments showing colocalization of SV2 or synaptophysin immunoreactivity and binding of WGA, a Golgi marker, in the perinuclear region (data not shown).…”
Section: Resultsmentioning
confidence: 75%
“…The disordered Golgi in nrc a14 photoreceptors would be predicted to cause a defect in trafficking newly synthesized synaptic proteins. Prior to reaching their destinations, many apical and basal proteins both pass through the trans Golgi [46]. However, the ability of nrc a14 cone photoreceptors to maintain proper apical trafficking despite altered Golgi morphology suggests that the disruption of protein transport of newly synthesized proteins is not the primary defect.…”
Section: Discussionmentioning
confidence: 99%